PENGEMBANGAN E-LKPD BERBASIS PROBLEM BASED LEARNING MENGGUNAKAN APLIKASI LIVE WORKSHEET PADA PEMBELAJARAN IPAS DIKELAS V SD - Estuhono, Estuhono; Ilham, Ahmad; Rizki Jayanti, Dian (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
The implementation of IPAS learning faces difficulties in students' understanding of the learning material, because teachers only focus on books and inadequate learning tools, resulting in students' lack of participation in the learning process. In order to confront this challenge, there is a necessity to integrate innovative learning methodologies and leverage technological advancements to develop learning tools in the form of E-LKPD.This research is classified as research and development. The development model employed is the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The E-LKPD was validated by lecturers from the Faculty of Teacher Training and Education, UNDHARI, with practicality assessed by observing the responses of educators and students, and effectiveness assessed from the results of the test questions provided. The research on the E-LKPD yielded a validation score averaging 87.75%, thus indicating its high validity. The practicality of the E-LKPD was assessed, yielding an average score of 84.50%, which is categorized as